SIMULATION ANALYSIS AND OPTIMIZATION DESIGN OF THE FLEXIBLE DYNAMICS OF A NEW TYPE OF WHEELCHAIR CLIMBING MECHANISM - ZHU Hua; YANG Hui (Jixie qiangdu)
Based on the design of a new type of automatic stair wheelchair,under the joint action of the drive motor torque and self-weight of users and wheelchair; we can obtain the stairs’ climbing time is 4. 3 second per level by calculation. Then with the help of the Transient Dynamic Module of ANSYS Workbench. Got movement characteristic curve of direct component mechanical foot 1 in the machine,and put forward the improvement scheme towards its unstable phenomenon; At the same time doing kinetics analysis,got the equivalent displacement of constructions of stair wheelchair and the change of time curve of equivalent stress of members of the gym agencies,completed kinematic analysis and dynamic analysis of mechanical system of flexible body of gym mechanism; Finally optimized the design of the ladder mechanism,the optimization result was reduced20. 74% than the quality of the original model,and reduced the manufacturing of raw materials,meanwhile provided theoretical basis for optimization design of this kind of wheelchair.